Extraction and encapsulation of bioactives coupled with nanocellulose production: an approach for comprehensive recovery of acerola by-products - Silva, Natalia Cristina da (2024)
Nanotechnology has expanded over the years, driven by the enhanced properties of nanoscale materials arising from their increased surface area. Simultaneously, the substantial amount of residual biomass generated from food processing raises concerns about environmental pollution. To synergistically connect these themes and enhance the value of biomass, agro-industrial by-products can serve as a source for extracting components used in the production of nanomaterial. In this context, the objective of this study was to fully use acerola by-products (peel and seeds) as raw material for the production of nanoencapsulated active extracts and nanocellulose. Firstly, acerola by-products were used as a source of extraction of total phenolic compounds (TPC), by using chitosan (Ch) suspension in different concentrations (0.4 1.0%, previously dissolved in 1% acetic acid) as an extracting solvent. Then, the extracts were encapsulated by ionic gelation, using sodium tripolyphosphate (TPP) dripping. The Ch concentration did not change the amount of TPC extracted, but it was an important factor in the size of the final particles and encapsulation efficiency. Particles produced with 0.8% Ch had a trimodal size distribution profile, but remained mostly on a nano/submicrometer scale (in the 127 and 920 nm ranges), and retained approximately 41% of the TPC. Furthermore, the compounds were released in a controlled manner into the exposure medium (approximately 75% in acidic medium and 25% in neutral medium) and did not affect the stability of the particles under accelerated centrifugation conditions. After this step, the remaining acerola by-product (RAB) from the extraction of TPC were characterized and presented approximately 37% of cellulose, 4% more than that found in the acerola by-product (AB) before extraction process. These results indicated that the use of the by-product after extraction of TPC facilitates cellulose isolation, probably due to mechanical (defibrillation) and chemical (solvent) effects of the process. The AB and RAB portions were chemically treated (pretreatment/bleaching), resulting in samples called AB_CT and RAB_CT, respectively. Then, the four raw materials (AB, RAB, AB_CT and RAB_CT) were subjected to acid hydrolysis to produce cellulose nanofibrils (CNF). CNFs based on RAB showed higher yield (CNF_RAB: 25.2% and CNF_RAB_CT: 24.2%), higher crystallinity index (CNF_RAB: 38.8% and CNF_RAB_CT: 71.7%) and higher thermal stability compared to CNFs extracted from AB and AB_CT. The results indicated that the use of the by-product after extraction facilitates the production of CNFs and can be strategic when less crystalline materials are desirable; or as a complementary step for more crystalline materials. In general, this study showed that it is possible to fully utilize the acerola by-product to produce two nanomaterials through a sustainable methodology, in which almost no waste is generated in the process. Among the different application possibilities (agricultural, pharmaceutical, food, textile), the use of these nanomaterials as edible coatings or packaging additives can have a significant impact on the circular economy.